A study on the impact of HIV/AIDS peer education program on the management of HIV and AIDS at the Kenya Ports Authority (KPA) - Kitala, Josephine Marura (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.